Correlation of pregnant oral health scoring models with inflammatory protein markers sCD14 and prostaglandins - Suwargiani, Anne Agustina; Aripin, Dudi; Arief, Erry Mochamad; Widyaputra, Sunardhi; Susilawati, Sri; Kadir, Rahimah Abdul (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: To analyse correlation of pregnant oral health scoring model with inflammatory protein markers sCD14 and prostaglandins.Method: A cross-sectional consisted of 80 pregnant women who met inclusion criteria used consecutive sampling.Result: The POSC-p model which was based on oral health scoring, components of salivary condition was significantly correlated with sCD14 and the POSC-p model and combined of oral health scoring was significantly correlated with prostaglandins.Conclusion: The POSC-p score model and the sCD14 of clinical examination have correlation consist of tooth decay, occlusion and salivary condition consist of salivary pH level, salivary volume and salivary buffer. However, there was no substantial correlation between the pregnant oral health scoring model of felt need and the pregnant oral health scoring for salivary conditions or the combined POSC-p score and sCD14 levels and POSC-p Scores (combined) significant correlation with sCD14